Seamless Mobility: Touchless Commuting - Rui Filipe Soares do Couto (2015)
This project envisions the development of a prototype of a wireless "validation system" for public transportation that could replace the current smart card validation concept. This makes the process of using public transports more fluid and simple for the users, while reducing operating costs for the providers. The system relies on the users' smartphones to relay relevant contextual information, regarding the public transport usage. One of the key focus points was the investigation of the existing communication wireless technologies, such as Bluetooth Low Energy, hardware and tools that could efficiently track the passengers' usage of the public transport. This represents an approach shift in public transportation - from checkin/checkout to be-in/be-out - which allows avoiding the former approach limitations.The work also focused on exploring the possible scenarios of deployment, taking in consideration several factors such as cost, versatility of the technology and possibility of fraud.The prototype was developed in the context of an actual public transportation system, in this case, Metro do Porto/STCP. Therefore, research was made on the current system to determine what was already implemented, what type of investment would have to be made and what would be the cost-benefit relationship. The similarity between this system and others around the world, allows the findings of this project to be a reference for future implementations of touchless commuting around the globe.The field test's results make it possible to believe in a solution based on Bluetooth Low Energy, as long as the technology keeps improving, the developed solution is refined and the tests are continued in cooperation with transportation operators.